ANALISIS PENGARUH INFRASTRUKTUR TERHADAP KETIMPANGAN PEMBANGUNAN EKONOMI WILAYAH DI PROVINSI ACEH - Muhammad Iqbal; Amzul Rifin; Bambang Juanda (TATALOKA, 2019)
Infrastructure development is an important aspect of economic growth. Good infrastructure development will ensure efficiency, facilitate the movement of goods and services, and increasing the added value of the economy, as well as factors driving the productivity of the area. The purpose of this study is to analyze the level of inequality between regions and analyze the effect of infrastructure availability on regional inequality in Aceh Province. The analysis method used is Williamson Index and Panel Data. The results showed that the significant variables can affect the imbalance of economic development of the region in Aceh province is the variable of electricity that has an effect of -0.012594 and the influential educational variables of -0.060347. Variables that have no significant effect is the road effect of -0.009463 and health variables affecting 0.046067.